2021
DOI: 10.1088/1361-6463/ac04e5
|View full text |Cite
|
Sign up to set email alerts
|

Metal particle induced spacer surface charging phenomena in direct current gas-insulated transmission lines

Abstract: The interpretation of the surface charge pattern of spacers in gas-insulated transmission lines (GIL) is a crucial and important research topic, which requires a comprehensive understanding of charge behaviors at physical interfaces. Here, we report a surface charging phenomenon of spacers in presence of metal particles inside the direct current (DC) GIL. The charging of spherical metal particle on the spacer surface appears as dotted discontinuously distributed charge spots which are due to the charge injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The model first ever introduces the concept of gas adsorption into the surface flashover, and the relative adsorption ability is crucial for the difference between surface flashover and gas breakdown voltages in compressed gas with various pressures and temperatures [126] . In 2021, Li et al [127] further established a numerical simulation model based on the synergetic effects of gas adsorption and surface charging and found the simulation results are consistent with experimental flashover voltage in nitrogen.…”
Section: Reviewmentioning
confidence: 85%
“…The model first ever introduces the concept of gas adsorption into the surface flashover, and the relative adsorption ability is crucial for the difference between surface flashover and gas breakdown voltages in compressed gas with various pressures and temperatures [126] . In 2021, Li et al [127] further established a numerical simulation model based on the synergetic effects of gas adsorption and surface charging and found the simulation results are consistent with experimental flashover voltage in nitrogen.…”
Section: Reviewmentioning
confidence: 85%
“…The exploration of highly sensitive online detection methods is a new challenge faced by researchers, and may also be a new direction for future research in this field [6]. Moreover, the charge accumulation at AC voltage, which has been discussed and verified by researchers in recent years, may result in a local electric field enhancement and lower the flashover voltage [21–27]. However, to the authors’ knowledge, there is still no direct evidence to verify this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The surface roughness of the samples before and after modification was measured by an optical profilometer (BRUKER GT-K), the water contact angle was measured by an optical contact angle meter (DAS 30), and energy dispersive x-ray analysis spectrometer (OCTANE PLUS) was used for elemental content analysis. Figure 1 depicts the experimental setup and samples [21]. The preprocessing process of the spacer surface before the experiment can be found in the previous paper [21].…”
Section: Experimental Descriptionsmentioning
confidence: 99%
“…Most recently, it was found that hetero-polar surface charge can be induced by metal particles, as shown in literature 21. The gas ionization near the particle tips introduces hetero-polar surface charge, and the trapped charge in turn polarizes homo-polar charges on the surface nearby, showing a concentrically distributed bipolar pattern [21]. Based on our recent test on an actual ±320 kV DC gasinsulated power transmission line (GIL), linear particles with length ranging from 5 mm to 15 mm have already started to 'jump' at +280 kV, which corresponds to an electric field of less than 1.5 kV mm −1 , much less than the average designed electric field inside the chamber [22].…”
Section: Introductionmentioning
confidence: 99%